Direct‐acting antiviral treatment for hepatitis C virus infection and risk of incident liver cancer: a retrospective cohort study. Issue 9 (7th March 2018) - Singer, A. W.; Reddy, K. R.; Telep, L. E.; Osinusi, A. O.; Brainard, D. M.; Buti, M.; Chokkalingam, A. P.
Summary: Background: Eradication of hepatitis C virus (HCV) infection via interferon‐based treatment lowers hepatocellular carcinoma risk; some research suggests this effect extends to interferon‐free treatment. Aims: The objective of this retrospective cohort study was to examine the association of direct‐acting antiviral (DAA) exposure with risk of incident liver cancer in real‐world data. Methods: From United States administrative claims data through March 31, 2017, we identified 30 183 adult HCV patients exposed to DAAs. For comparison, we identified contemporary adult HCV patients without evidence of HCV treatment (N = 137 502), and historical HCV patients treated with interferon prior to the introduction of DAAs (N = 12 948). Included patients had at least 12 months of prior enrolment and no evidence of prior liver cancer at baseline. Hazard ratios (HRs) estimating risk of incident liver cancer associated with DAA treatment were calculated using Cox proportional hazards methods. Results: Relative to untreated HCV patients, DAA‐treated patients were older, more likely to be male, and more likely to have cirrhosis at baseline. After adjustment, DAA treatment was associated with a significantly reduced risk of liver cancer relative to no treatment (adjusted HR = 0.84, 95% CI: 0.73‐0.96), and relative to interferon‐based treatment in the pre‐DAA era (HR = 0.69, 95% CI: 0.59‐0.81). Conclusions: In this large, population‐based study, DAA‐based treatment was associated with a reduced risk of incident liver cancer relative to both no HCV treatment and to interferon‐based treatment in the pre‐DAA era. As additional follow‐up time of DAA‐treated patients accrues, we anticipate that the long‐term benefits of DAA treatment will become more apparent. Abstract : Linked Content This article is linked to Hussaini et al, Mahla et al and Singer et al papers. To view these articles visithttps://doi.org/10.1111/apt.14634, https://doi.org/10.1111/apt.14795 andhttps://doi.org/10.1111/apt.14820 .